Place of study, field of study and labour-market region: What matters for wage differences among higher-education graduates? - Silvia Kopecny; Steffen Hillmert (Journal for Labour Market Research, 2021)
This paper focuses on the structure and extent of wage differences among graduates of different higher-education institutions in Germany. We ask how large these differences are and how they relate to fields of study and regional labour markets. The results from our application of cross-classified random-effects models to a cohort of the DZHW Graduate Panel show that there is a considerable amount of wage variation depending on the graduates' alma mater. However, this variation can be fully explained by structural characteristics: Selection based on individual characteristics is of only minor importance, while regional labour markets do matter. Most of all, however, the differences relate to fields of study.
Keywords: E24; I23; I26; J31; 330; Wages; Higher-education institution; Fields of study; Regional labour markets; Multi-level analysis